Free distribution of condoms to female sex workers in Ecuador: effects on purchase behavior - Fernández, Mario (Revista Chilena de Salud Pública, 2015)
Condoms are considered an effective method to prevent the spread of sexually transmitted infections. In Ecuador, a common factor in sexual health public policy is the provision of free condoms to female sex workers. This occurs together with advice on other preventive measures and the importance of HIV screening. The present study seeks to determine whether the distribution of free condoms affects their purchase and subsequent use. A survey to assess condom purchase behavior was completed by 2566 female sexual workers (FSW) in eight cities in Ecuador. The Frontiers Prevention Project (FPP) conducted surveys during 2006. There is a risk of sample selection bias as access to public policy and free condoms is not random: we therefore used a Heckman estimation procedure in two stages. The probability of purchasing condoms and the quantity of condoms purchased were analyzed. We find that for each condom received for free, FSW purchased one more. This result shows the effectiveness of distribution policies when they are accompanied by advice and information.